2017
DOI: 10.1044/2016_jslhr-l-16-0297
|View full text |Cite|
|
Sign up to set email alerts
|

Language Development and Impairment in Children With Mild to Moderate Sensorineural Hearing Loss

Abstract: Clinically significant language impairments are not an inevitable consequence of MMHL. Risk factors appear to include lower maternal education and family history of language problems, whereas nonverbal ability may constitute a protective factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 75 publications
1
58
0
2
Order By: Relevance
“…Despite the fact that AABR was considered the best test for NHSP, [44][45][46][47] most of the respondents believed it to be OAE. This could be because OAE is well known to most physicians as being a more reliable and quick method of hearing screening than AABR.…”
Section: Knowledge Of Hearing Testsmentioning
confidence: 99%
“…Despite the fact that AABR was considered the best test for NHSP, [44][45][46][47] most of the respondents believed it to be OAE. This could be because OAE is well known to most physicians as being a more reliable and quick method of hearing screening than AABR.…”
Section: Knowledge Of Hearing Testsmentioning
confidence: 99%
“…Mayberry [17] and Mayberry and Lock [18], for instance, documented differences in language development and language outcomes for children who were exposed to ASL early in life as compared to those exposed to ASL later. However, such differences are not only present in those who go on to use ASL: there is also potential for children with even a mild to moderate hearing loss and who use primarily or only spoken language to experience the effects of language delay [19]. Other researchers have found a strong relationship between language proficiency (regardless of modality) and literacy among older d/hh learners [3,4,[20][21][22].…”
Section: Language Delay and Deprivation And Literacymentioning
confidence: 99%
“…NWR has been found to be difficult for children with all degrees of HI wearing CI or HA, both regarding segmental features (Briscoe et al, 2001;Dillon, Cleary, Pisoni, & Carter, 2004;Halliday et al, 2017), and prosody (Carter, Dillon, & Pisoni, 2002). NWR may further be a good predictor of language development in children with CI (Nittrouer, Caldwell-Tarr, Sansom, Twersky, & Lowenstein, 2014).…”
Section: Word and Nonword Repetition In Children With Hearing Impairmentmentioning
confidence: 97%
“…High nonverbal intelligence and faster verbal rehearsal speed also provide advantages for language development (Geers & Sedey, 2011). Halliday, Tuomainen, and Rosen (2017) found that oral and written language abilities were not linked to the severity of HI, or to age of HI identification, in children with mild to moderate HI aged 8-16. Instead, speech and language performance was predicted by familial language problems, maternal education, and nonverbal ability.…”
Section: Development Of Speech Language and Cognitionmentioning
confidence: 99%
See 1 more Smart Citation